Legal Politics: Between the Reform and the Transformation of Islamic Family Law - Siregar, Rika Diana (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
This research discusses the dynamics of legal politics in the context of Islamic family law reform and transformation. The main focus of this study is how the direction and pattern of changes in Islamic family law are influenced by state policies, social pressures, and responses to the demands of modernity and gender justice. Using a juridical-normative approach and qualitative analysis of legal documents, public policy, and academic discourse, this study identifies two main trends: reform as a normative renewal within the existing legal framework, and transformation as a more profound paradigm shift towards the structure and basic values of Islamic family law This study finds that there are variations in models in the excavation, practice and reform of family law in the world Islam. Variations were also found when the Islamic world carried out the process of transforming family law into national law. The impact of the reform and transformation of family law in Indonesia is that the classical fiqh books that were originally used as the main reference and considered sacred, have lost their sacredness. However, the reform and transformation of family law in Indonesia has not reduced the independence of religious judges in exploring and finding more contextual Islamic law. This research is expected to make a conceptual contribution in formulating a political and legal direction that is responsive, fair, and rooted in progressive Islamic values.